EFFICACY OF SINGLE DOSE VERSUS MULTIPLE DOSE ANTIBIOTIC IN ELECTIVE INGUINAL HERNIA SURGERIES - Dr. Girish B. K; Dr. Harish. C; Dr. Hemand N. M; Dr. Shibin Sankar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
A hernia is an abnormal protrusion of the whole or part of a viscus through normal or abnormal opening in the walls of its containing cavity.1 Inguinal hernias are among the most common problems seen in surgical clinics. Inguinal hernias comprise 75% of all abdominal hernias.The lifetime risk of developing an inguinal hernia is 27% in males.The lifetime risk of developing an inguinal hernia is 3% in females2. They can be congenital or acquired, complete or partial, external or internal, reducible or irreducible, direct orindirect, and primary or recurrent3. Patients typically present with a bulge in the groin that is associated with pain in twothirds of cases.4 Painful hernias are most frequently described as a dull aching, heavy, dragging, or burning sensation. Maneuvers thatincrease intra-abdominal pressure, such as straining, lifting, or coughing, may exacerbate pain or hernia size by causing intra-abdominal contents to be pushed through the fascial defect5.Some patients may complain of worsening symptoms at the end of the day or after increased activity. Minor symptomatic cases may be temporarily improved by lying down or reducing the hernia manually. Severe or unbearable pain, that is, sudden onset, suggests possible complicated hernia and should be treated as an emergency.